Prednisone USE IN PATIENTS WITH ASTHMA BRONKHIALE linked IgE AND IgG LEVELS PATIENTS - Tjandra, Lusiani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Background: Thereâs been reported that the use of prednisone increase the occurrence ofÂ disease caused by viruses. And so, this study was done to find out the IgG and IgE status in asthmaticÂ bronchial patients who used prednisone.Methods: The immunodiagnostic test applied was the precipitation test.Results: Showed that the average of IgG in asthmatic bronchial patients who used prednisoneÂ is 1332,09 mg/dl, less than the average IgG in patients who did not use prednisone. The average of IgEÂ in asthmatic bronchial patients who used prednisone is 4224,0.10-5mg/dl, less than the average of IgEÂ in patients who did not use prednisone. The use of prednisone as a therapy for asthma bronchiale doesÂ lower the rate of IgG but that rate is still within the range of normal IgG rate in human body (639 âÂ 1349 mg/dl).Conclusions: So, the use of prednisone canât make human suffers from diseases cause byÂ viruses just because the use of prednison as a therapy in asthma bronchiale.